The effects of postactivation potentiation on sprint and jump performance of male Academy soccer players - Till, K. A.; Cooke, C. (The Journal of Strength and Conditioning Research, 2009)
The purpose of this investigation was to evaluate the postactivation potentiation (PAP) effects of both dynamic and isometric maximum voluntary contractions (MVCs) on sprint and jump performance and establish whether PAP methods could be used effectively in warm up protocols for soccer players. Twelve male soccer players performed 4 warm up protocols in a cross-over, randomized, and counterbalanced design. In addition to a control warm up, subjects performed deadlift (5 repetitions at 5 repetitions maximum), tuck jump (5 repetitions), and isometric MVC knee extensions (3 repetitions for 3 s) as PAP treatments in an otherwise identical warm up protocol. After each treatment, the subjects underwent 3 10 m and 20 m sprints 4, 5, and 6 minutes post-warm up and 3 vertical jumps (VJ) at 7, 8, and 9 minutes post-warm up. Repeated measures analysis of variance showed no significant differences in the first 10 m (p = 0.258) and 20 m (p = 0.253) sprint and VJ (p = 0.703) performance and the average 10 m (p = 0.215), 20 m (p = 0.388), and VJ (p = 0.529) performance between conditions. There were also no significant differences in performance responses between the strongest and weakest subjects, but large variations in individual responses were found between the subjects. The findings suggest that there was no significant group PAP effect on sprint and jump performance after dynamic and isometric MVCs compared with a control warm up protocol. However, the large variation in individual responses (-7.1% to +8.2%) suggests PAP should be considered on an individual basis. Factors such as method, volume, load, recovery, and interindividual variability of PAP must be considered in the practical application of PAP and the rigorous research design of future studies to evaluate the potential for performance enhancement.